Extremely High Frequency Resolution and Low Harmonic Distortion Digital Look-Up-Table Sinusoidal Oscillators - M. M. Al-Ibrahim (Jarrah) (Active and Passive Electronic Components)
New techniques to efficiently increase the frequency resolution of digital sinusoidal oscillators based on look-up-table (LUT) methods are proposed. The increase in frequency resolution is achieved while maintaining very low level of spurious harmonic distortion. The proposed techniques increase the LUT length to a level at which the spurious harmonic distortion is negligible. The first proposed technique is based on partitioning the address register into three sets and dividing the available LUT length into three smaller tables addressed according to the content of the address register sets. The second proposed technique utilizes one LUT and interpolates the values of the samples that are not stored in the table. The third proposed technique is similar to the first technique with the advantage of simpler implementation and lower levels of spurious harmonic distortion. The proposed techniques are simulated and their performance is compared with that of the direct LUT and trigonometric interpolation methods. The simulation results show that the proposed techniques are superior to both direct LUT and trigonometric interpolation methods.